The socio-material construction of users : 3d printing and the digitalization of the prosthetics industry - Seibt, David (Abingdon, Oxon ; New York, NY : Routledge, 2023)
"This book explores the intricate connections that link the current digitalization of manufacturing to our daily lives and identities as members of highly technologized societies. Based on extensive research on the prosthetics industry in Germany, the USA, Canada, and Haiti, the author demonstrates the socio-material construction of users, examining the ways in which the introduction of 3D printing changes how artificial limbs are designed, manufactured, distributed and used. Addressing questions surrounding the capacity of flexible production to afford greater diversity of user roles, and the likelihood of 3D printing allowing for open-source hardware and the democratization of production, the author presents a theory of digitalization that sheds light on the dynamics of industrial transformation and the future of use. An empirically grounded and conceptually informed study, The Socio-Material Construction of Users will appeal to researchers in the fields of sociology, science and technology studies and organization studies, as well as readers interested in 3D printing and the digitalization of society"--
Introduction: How Do User Roles Change in Digitalizing Industries? -- Theoretical Foundations of Industrial User Construction -- Methods for Studying Industrial User Construction -- Designing Technology: User Representation and Inscription -- Distributing Technology: Mediation between Industry and Users -- Using Technology: Between Re-Interpretation and Re-Inscription -- Digitalization and the Future of Use.
Keywords: Prosthesis industry; Artificial limbs -- Economic aspects; Three-dimensional printing